Silent Pulmonary Embolism in Deep Vein Thrombosis: Relationship and Risk Factors. (October 2022) - Shi, Yadong; Wang, Tao; Yuan, Yuan; Su, Haobo; Chen, Liang; Huang, Hao; Lu, Zhaoxuan; Gu, Jianping
Purpose: This study aimed to evaluate risk factors for silent pulmonary embolism (PE) in symptomatic deep vein thrombosis (DVT) and investigate the relationship between DVT and silent PE. Methods: This was a single-centre, retrospective cohort study. Between 5 January 2015 and 31 December 2021, consecutive patients with symptomatic DVT received CT pulmonary angiography and CT venography were analyzed. Patient demographics, comorbidities, risk factors, and image findings were analyzed. The group differences were compared using a Chi-square test, Fisher's exact test, independent t test, or Mann-Whitney U test. Multivariant regression was used to determine predictive factors for silent PE. Results: A total of 355 patients (mean age, 60.5 ± 16.6 years) were included. The incidence of silent PE was 43.1%. The main or lobar pulmonary arteries were affected in 53.6% of patients, which is more often found in iliofemoral DVTs (56.6% vs 26.7%, p  = .027). The multivariant analysis showed male patients ( p  = .042; OR 1.59; 95% CI, 1.02–2.50), inferior vena cava involvement ( p  = .043; OR 1.81; 95% CI, 1.02–3.20) and D-dimer value   >   3.82 μg/ml ( p  <   .001; OR 2.32; 95% CI, 1.43–3.77) were risk factors for silent PE. Unilateral DVT patients with ipsilateral iliac vein compression had a lower incidence of silent PE (28.8% vs 52.9%, p <  .001). Conclusion: Iliofemoral DVT was associated with a more proximal PE. The male patients, inferior vena cava involvement, and D-dimer   >   3.82 μg/ml were risk factors for silent PE. Ipsilateral iliac vein compression reduced the incidence of silent PE.